Virtual Lab Module Feature Development on ETHOL System for PHP Learning - Sherly Maya Salsabilla; Mirta Chadhirotin Nachlah (Journal of Advanced Vocational Information and Communication Technology, 2026)
Information technology in education has rapidly evolved, particularly in supporting distance learning systems. However, conventional e-learning platforms often lack practical components, limiting students’ ability to develop hands-on skills. This study addresses the need for an interactive learning environment by developing a virtual laboratory focused on PHP programming. The proposed system enables students to perform practical exercises in a web-based environment, simulating real laboratory activities. The virtual lab is integrated with the existing Learning Management System through web services, specifically ETHOL (Enterprise Technology Hybrid Online Learning) at EEPIS. The implementation of this system provides flexibility for students to access learning materials and conduct experiments anytime and anywhere. The results indicate that the virtual lab enhances students’ understanding of programming concepts and supports independent learning. Load testing demonstrated that the system handles 4,638 requests within 3 minutes with an average response time of 26 ms and a throughput of 27 requests per second on minimal cloud hardware (1 GB RAM, 1 vCPU). Responsiveness testing confirmed that the website functions properly on 100% of tested devices (2 desktop and 1 mobile resolutions). Therefore, the developed virtual lab can serve as an effective complementary tool in e-learning environments.